MAINTENANCE PLANNING FOR HAAS ST-10 CNC LATHES IN THE COVID-19 PANDEMIC ERA BASED ON INTERVAL TIME MAINTENANCE - Suryo, Sumar Hadi (JEMIS (Journal of Engineering & Management in Industrial System), 2022)
CNC machines are machines that apply a close-loop system where errors in the machine can be detected automatically via an alarm code. CNC Lathes in operation are inseparable from the maintenance and maintenance processes carried out by both machine operators and technicians in the maintenance field. In the era of Covid-19 pandemic, maintenance and maintenance policies were still carried out even though the production intensity was different under normal conditions. In this study, a maintenance strategy planning was carried out in the pandemic era of the CNC HAAS ST-10 lathe, the maintenance strategy planning was carried out based on the machine maintenance time interval and the machine working time that was different from normal conditions, from 8 working hours to 6 working hours. In addition to maintaining machine performance to stay prime, the HAAS ST-10 CNC lathe maintenance strategy is carried out to reduce maintenance costs in covid-19 conditions.